2020
DOI: 10.1111/tbed.13691
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of pestiviruses isolated from bovine, ovine and caprine foetuses in Turkey: A potentially new genotype of Pestivirus I species

Abstract: This study was carried out to investigate the frequency and genetic diversity of pestiviruses in abortion cases in cattle and small ruminants in Turkey. During January 2012 and December 2017, a total of 2029 aborted foetuses (553 bovine foetuses, 1,388 sheep foetuses and 88 goat foetuses) were collected from different regions of Turkey. Real-time RT-PCR (RRT-PCR) assays were used to detect pestiviral RNA in aborted foetuses. To confirm the cause of abortion, pestivirus-positive foetuses were also examined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
1
6
0
4
Order By: Relevance
“…Sequence identity between OVPV and CSFV was as high as 89.9% in the 5 UTR region. These results revealed that the Italian OVPV is more closely related to CSFV than BDV, BVDV, or any other of the existing or recently-discovered pestiviruses, such as Aydin, LINDA, or APPV [12][13][14].…”
Section: Introductionmentioning
confidence: 81%
“…Sequence identity between OVPV and CSFV was as high as 89.9% in the 5 UTR region. These results revealed that the Italian OVPV is more closely related to CSFV than BDV, BVDV, or any other of the existing or recently-discovered pestiviruses, such as Aydin, LINDA, or APPV [12][13][14].…”
Section: Introductionmentioning
confidence: 81%
“…In sheep, abortions can be caused by viral [1,2] bacterial [3,4] or parasitic [5,6,7] factors, as well as diet deficiencies [8], poisoning [9] and extreme weather conditions [10]. Furthermore, in addition to the significant economic losses [11], any deaths caused by zoonotic pathogens can also pose a risk to breeders, animal keepers or veterinarians [12].…”
Section: Introductionmentioning
confidence: 99%
“…[22] Karadeniz Bölgesinde sığır ve koyunlarda abort yapmış fötuslarda pestivirus genom varlığını RT-PCR testi ile araştırmış ve sığır fötuslerinde (6/21) %28,57, koyun fötuslerinde (14/21) %66,66 oranlarında varlığını tespit etmişlerdir. Şevik [23], Türkiye'nin İç, Ege ve Akdeniz Bölgesinden sağladığı abort yapmış sığır, koyun ve keçi fötuslerinde pestivirus varlığını RT-PCR testi ile araştırmış, sığırlarda (61/553) %11, koyunlarda (124/1388) %8,9 ve keçilerde (3/88) %3,4 oranlarında abort etiyolojisinde pestivirus payını tespit etmiştir. Bu araştırma Doğu ve Güneydoğu Anadolu Bölgelerinde yetiştirilen sığır, koyun ve keçi sürülerinde abort yapmış fötuslada etiyolojideki pestivirus oranını tespit edildiği ilk çalışma olması nedeni ile önem arz etmektedir.…”
Section: Introductionunclassified